Homens infames : práticas em um espaço inventado como fronteira - Silva, Reinaldo Norberto da (2012)
This paper aims to contribute to studies on the emergence of Biopower in the Province of Mato Grosso. Thus, we concur with our research from the town of São Luiz de Cáceres, on the border with the Province of the Republic of Bolivia, during the nineteenth century. In this field, we seek to understand the discourses and practices in circularity in this space, highlighting the ways the construction of the border as a place of violence, crime and disorder. And later, we shirk this speech pre-determined, the sources insist highlight, to give visibility and dizibilidade the practices of those guys who circulate in this space. Appearing at this time, the jokes as social space buddies, household, soldiers, planters, ie, all these characters lives infamous.